Strategi Pengembangan Usahatani Nanas Pada Kelompok Tani Sinjay Di Desa Astomulyo Kecamatan Punggur, Lampung Tengah - M. Lathiifu Razzaq; Supriyadi Supriyadi; Ainul Mardliyah; Fikri Syahputra (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2022)
This study aims to determine the appropriate development strategy in an effort to increase pineapple farming in the Sinjay Farmer Group in Astomulyo Village Punggur District Central Lampung Regency. This research was conducted at the Sinjay Farmer's Group in Astomulyo Village Punggur District Central Lampung Regency. The number of samples in this study were 55 pineapple farmers and all of them were used as samples. The sampling method uses the saturated side (census) for all farmers in the population. The analytical method used in this research is SWOT analysis to find out the existing internal and external factors. The results of this study indicate that based on the results of the analysis on the SWOT matrix, the recommendation that must be given is the